Variation of in vitro digestibility of pea protein powder dispersions from commercially available sources. (1st February 2023) - Jiménez-Munoz, L.; Torp Nielsen, M.; Roman, L.; Corredig, M.
Highlights: Pea protein isolates suspensions showed different microstructure. All isolates showed similar degree of hydrolysis in in vitro digestion. Processing history showed differences in amino acid release. Different commercial isolates have different breakdown kinetics. Abstract: With raising consumer demand for plant-derived proteins, there has been an increased interest in the utilization of pea ingredients in food formulations. It was hypothesized that differences in processing history and composition affect their colloidal properties and their breakdown during in vitro simulated gastrointestinal digestion. The gastrointestinal fate of three different commercial pea protein ingredients, two protein isolates and one less refined concentrate was compared. The concentrate dispersion showed greater solubility, different protein composition and smaller particle size than the reconstituted pea protein isolates. When heat-treated, the release of free amino groups decreased for the isolates, but increased for the concentrate dispersions. LC-TQMS of free amino acids in the intestinal digestates indicated a significantly higher release of methionine (limiting amino acid in pea protein) in the concentrates than in the isolates. This work highlights the influence of processing and composition on techno-functional and digestion properties of pea ingredients.